Kyai Haji Ahmad Dahlan: Pendiri Muhammadiyah dan Pembaharu Pendidikan Islam di Indonesia - Mustofa, Ahmad Al; Khotimah, Anisa Nur (TSAQOFAH, 2025)
This paper discusses the role and thoughts of Kyai Haji Ahmad Dahlan, an Islamic reformer in Indonesia who founded Muhammadiyah. This research aims to examine his contribution to the reform of Islamic education and his influence in social and religious life. Using a descriptive qualitative approach, this paper compiles data from literature and primary sources on Ahmad Dahlan's life and thought. The results show that Ahmad Dahlan had a great vision in integrating Islamic values with modern education. Through Muhammadiyah, he developed an education system that combined religious and general knowledge, making it relevant to the challenges of the times. His thinking was not only limited to education, but also touched on social aspects such as community empowerment and religious reform. This paper emphasises the importance of Ahmad Dahlan's role in the history of Islamic renewal in Indonesia. His thoughts and contributions remain relevant in the context of education and Islamic community development to this day.